Effect of rejuvenation pruning on the yield of different cultivars in a super high density olive orchard - Dias, António F. (2019)
The adequacy of the olive canopy dimensions to the over-the-row harvesting machinery is one of the most important management practices in super high density olive orchards (SHD). Manual pruning performed every year can control canopy dimension and also tree exposure to sunlight. An adequate balance between the removal of woody non-productive branches and the maintenance of a large amount of reproductive shoots is required. When an excessive canopy development occurs, a severe pruning intervention can be a solution to recover the orchard productivity. This paper presents the results obtained after rejuvenation pruning of a SHD orchard with excessive canopy dimension. The SHD orchard was established in March 2002 in Herdade dos Lameirões – Safara - Moura - Portugal (38º 04’N 7º 16’W). The orchard is planted according a randomised complete block design with three replications. The orchard has two densities, 1850 trees per hectare (4m×1.35m) and 1250 trees per hectare (4m × 2m) planted with six varieties (‘Azeiteira’, ‘Cobrançosa’, ‘Cordovil de Serpa’, ‘Galega vulgar’, ‘Redondil’, ‘Arbequina’), leading to 36 plots each composed of 3 rows. The pruning was performed in April 2010. It consisted in a mechanically topping of the canopy parallel to the ground at 2.5m high and hedging of each side close to the central leader of the trees, followed by a manual pruning complement to remove the remaining branches. The olive production was recovered in the second year after pruning. Significant differences were found among results of the different years and among the varieties, with regard to olive yield per hectare. The highest yield was registered in the third year after pruning. Planting density had a significant effect on yield per tree with higher production in the 4m x 2m array.